2015
DOI: 10.1016/j.livsci.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Variables of gait inconsistency outperform basic gait variables in detecting mildly lame cows

Abstract: a b s t r a c tTo support herdsmen in finding the lame cows on their herds, several automated systems that measure lameness related cow features such as gait patterns, are being developed. Most of these systems are able to distinguish between non-lame and severely lame cows. Detecting mildly lame cows in an early stage of lameness however seems challenging. Inspired by the approach used in human gait research, new variables that measure the inconsistency in stride-to-stride variables were tested using cow gait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Van Nuffel et al (2015c) reported that stride length (meters) and duration (seconds) were indicative of lameness using the Gaitwise pressure mat system, a research tool described in Maertens et al (2011). Using the Gaitwise system, stance time (weight-bearing) for the nonlame leg was also found to be longer in lame cows (Van Nuffel et al, 2013, 2015a. Lame cows are relatively cautious or careful about affected foot placement as this action is thought to be painful (Van De Gucht et al, 2017b).…”
Section: Variables Indicative Of Lamenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Nuffel et al (2015c) reported that stride length (meters) and duration (seconds) were indicative of lameness using the Gaitwise pressure mat system, a research tool described in Maertens et al (2011). Using the Gaitwise system, stance time (weight-bearing) for the nonlame leg was also found to be longer in lame cows (Van Nuffel et al, 2013, 2015a. Lame cows are relatively cautious or careful about affected foot placement as this action is thought to be painful (Van De Gucht et al, 2017b).…”
Section: Variables Indicative Of Lamenessmentioning
confidence: 99%
“…These variables were generally averages. Measures of inconsistency have also been proposed by some researchers citing its use in human gait research (Van Nuffel et al, 2015a). Inconsistency in this context is the extent a step varies from one to the next.…”
Section: Variables Indicative Of Lamenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobility scoring is one example of a subjective technique used by herdsmen to identify lameness and locomotors problems in dairy cows [7]. Although cheap to disseminate, mobility scoring is time-consuming and must be done regularly [9][10]. Another criticism of the technique is that it may fail to identify the early (sub-clinical) stages of lameness [11][12].…”
Section: A Framework For Real-time Cattle Monitoring Using Multimediamentioning
confidence: 99%
“…On top of that, lack of application of visual locomotion scoring in practice often results in bad diagnoses, untreated lameness, and associated losses. To solve this problem, research started on the development of automatic lameness detection systems using a wide range of sensor techniques such as cameras (Nikkhah et al, 2005;Viazzi et al, 2013;Van Hertem et al, 2014), pressure plates (Neveux et al, 2006;Chapinal et al, 2009), pressure mats (Maertens et al, 2011;Van Nuffel et al, 2015), and accelerometers (Chapinal et al, 2009;Pastell et al, 2009). Research, however, has principally focused on sensor development and data interpretation (Rutten et al, 2013), whereas studies on the economic added value of such systems for farmers are scarce.…”
Section: Introductionmentioning
confidence: 99%